The human rights of migrants and refugees in European law - Costello, Cathryn (Oxford : Oxford University Press, 2016)
A critical discussion of EU and ECHR migration and refugee law, this book analyses the law on asylum and immigration of third country-nationals. It focuses on how the EU norms interact with ECHR human rights case law on migration, and the pitfalls of European human rights pluralism.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 26, 2016).
Keywords: Emigration and immigration law -- European Union countries; Refugees -- Legal status, laws, etc. -- European Union countries; Human rights -- European Union countries; Law; Laws of specific jurisdictions & specific areas of law